1996
DOI: 10.1104/pp.112.3.1253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature on Photosynthesis in Beans (II. CO2 Assimilation and Metabolite Contents)

Abstract: The effect of high temperatures on CO, assimilation, metabolite content, and capacity for reducing power production in nonphotorespiratory conditions has been assessed in two different bean (Phaseolus vulgarus 1.) varieties, Blue Lake (commercially available i n the United Kingdom) and Barbucho (a noncommercially bred Chilean variety), which are known to differ in their resistance to extreme high temperatures. Barbucho maintains its photosynthetic functions for a longer period of time under extreme heat compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 33 publications
2
42
1
1
Order By: Relevance
“…For example, Andrade et al (1992) showed that the temperature from 15 to 188C during the vegetative period caused low RUE in maize. Also, high temperature (increased respiration sometimes above the rate of photosynthesis) had negative effects on crops (Pastenes and Horton 1996;Monneveux et al 2003). In a previous study, decreased precipitation as combined with high temperature showed a considerable negative effect on pasture production in southern Mongolia (Munkhtsetseg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Andrade et al (1992) showed that the temperature from 15 to 188C during the vegetative period caused low RUE in maize. Also, high temperature (increased respiration sometimes above the rate of photosynthesis) had negative effects on crops (Pastenes and Horton 1996;Monneveux et al 2003). In a previous study, decreased precipitation as combined with high temperature showed a considerable negative effect on pasture production in southern Mongolia (Munkhtsetseg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature regulates most of the basic aspects of cell metabolism; high temperatures denature enzymes and lower temperatures freeze tissues and damage cell membranes (Palta et al, 1993;Pastenes and Horton, 1996). Furthermore, most plants grow best when temperatures fluctuate at least a 6 to 7 ºC between day and night (Lüttge, 2004).…”
Section: Raiza J Castillo Et Almentioning
confidence: 99%
“…These groups suggest that Rubisco deactivation at high temperature may be a regulatory response to the limitation of one of the processes contributing to electron transport capacities. For example, at high temperature, protons can leak through the thylakoid membrane, impairing the coupling of ATP synthesis to electron transport (Pastenes and Horton, 1996;Bukhov et al, 1999Bukhov et al, , 2000. As the electron transport capacity becomes limiting, ATP/ADP ratios and the redox potential of the chloroplast decline, causing a loss of Rubisco activase activity and, in turn, a reduction in the Rubisco activation state (Zhang and Portis, 1999;Zhang et al, 2002;Sage and Kubien, 2007).…”
mentioning
confidence: 99%